1996
DOI: 10.1182/blood.v87.5.1912.bloodjournal8751912
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of 11q23 breakpoints within the MLL breakpoint cluster region in de novo acute leukemia and in treatment-related acute myeloid leukemia: correlation with scaffold attachment regions and topoisomerase II consensus binding sites

Abstract: A major unresolved question for 11q23 translocations involving MLL is the chromosomal mechanism(s) leading to these translocations. We have mapped breakpoints within the 8.3-kb BamHI breakpoint cluster region in 31 patients with acute lymphoblastic leukemia and acute myeloid leukemia (AML) de novo and in 8 t-AML patients. In 23 of 31 leukemia de novo patients, MLL breakpoints mapped to the centromeric half (4.57 kb) of the breakpoint cluster region, whereas those in eight de novo patients mapped to the telomer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
100
0
4

Year Published

2002
2002
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(109 citation statements)
references
References 0 publications
5
100
0
4
Order By: Relevance
“…Herein, we have shown, for the first time, that Mll genomic fusions can be induced by etoposide in murine cells. In human leukemias, MLL translocation breakpoints are localized to an 8.3 kb BCR encompassing exons 5−11 (23). Using murine/human Mll exonic homology as a guide, we positioned the Mll primers to encompass up to 11.7 of a putative murine Mll BCR and detected a number of intra-and inter-chromosomal fusions.…”
Section: Discussionmentioning
confidence: 99%
“…Herein, we have shown, for the first time, that Mll genomic fusions can be induced by etoposide in murine cells. In human leukemias, MLL translocation breakpoints are localized to an 8.3 kb BCR encompassing exons 5−11 (23). Using murine/human Mll exonic homology as a guide, we positioned the Mll primers to encompass up to 11.7 of a putative murine Mll BCR and detected a number of intra-and inter-chromosomal fusions.…”
Section: Discussionmentioning
confidence: 99%
“…Several mechanisms of specific DNA breakage have been implicated in the genesis of translocations. There is considerable circumstantial evidence to suggest that breakpoints within the MLL gene, at least in a subset of cases, may be caused by interference with the action of topoisomerase II, by either environmental or dietary compounds (Wiemels and Greaves, 1999;Strick et al, 2000;Alexander et al, 2001) or by previous treatment with epipodophyllotoxins (Broeker et al, 1996). Translocations in lymphoid malignancies have long been postulated to be a consequence of aberrations in the mechanism that recombines immunoglobulin or T-cell receptor genes, although studies of the t(14;18) have suggested that the process may in fact be more complex (Jäger et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Microcluster 1 had three potential minor translin binding sites between positions 231 and 248 (two mismatches) and 244 and 259 (one mismatch) on the forward strand and between positions 232 and 249 (two mismatches) on the reverse strand. Microcluster 3 contained several sequence elements: (i) a high-stringency topoisomerase II site (Broeker et al, 1996) between positions 13313 and 13330 on the forward strand; (ii) two minisatellite core sequences, each with one mismatch and each on the reverse strand (positions 13145-13154 and 13538 -13547), with the second site conforming perfectly to a chi-like sequence; (iii) a major translin site (forward strand, two mismatches, positions 13416 -13433); and (iv) two minor translin sites, one on the forward strand between positions 13633 and 13647 (two mismatches) and one on the reverse strand between positions 13624 and 13638 (two mismatches). Overall, there were 43 major and 48 minor translin sites in RARA intron 2, with up to two mismatches from the published consensus sequences.…”
Section: Sequence Features Within Rara Intronmentioning
confidence: 99%
“…Etoposide is a well-established inhibitor of topo II, promotes DSBs across the genome as well as specifically within the MLL bcr, and promotes MLL chromosomal translocations (Blanco et al, 2003;Libura et al, 2005;Felix et al, 2006). MLL breakpoint sequences associated with infant acute leukemia are similar to those in t-AML following etoposidecontaining regimens (Super et al, 1993;Broeker et al, 1996). Thus, it has been hypothesized that exposure to biochemically similar compounds including bioflavonoids may contribute to infant leukemia from in utero exposure from maternal diet (Ross, 2000;Vanhees et al, 2011;Bariar et al, 2013).…”
Section: Introductionmentioning
confidence: 99%